Nevirapine and the quest to end pediatric AIDS - Anderson, Rebecca J. (Rebecca Jane), 1949- (McFarland & Company, Inc., Publishers, 2014)
"In 1999, investigators announced that a single dose of nevirapine, a new antiviral drug, could stop the spread of the AIDS virus from infected mothers to their newborn babies. It was a discovery that "changed the face of AIDS globally" but it came at a high price"--